Digital and interactive school mathematics - Vanegas Ibáñez, Nelsy Carolina; Valbuena Duarte, Sonia; Berrío Valbuena, Jesús David (Rastros Rostros, 2024)
This study explores the impact of digital interactive booklets on the understanding and academic performance in mathematics of eighth-grade students. Faced with persistent difficulties in mathematics and low academic performance on objective tests, an educational intervention is proposed through the implementation of attractive and adaptive digital materials. The purpose of the project is to improve the understanding of fundamental mathematical concepts, taking advantage of the students’ affinity, who are digital natives, for interactive technologies. Adopting a qualitative approach and working in stages, digital mathematical booklets were designed and applied to address problem areas identified through previous diagnostics. Preliminary findings indicate a positive impact on objective tests, suggesting the effectiveness of this innovative approach. This study contributes to the field of mathematics education by demonstrating how interactive technological resources can be effectively used to strengthen the teaching and learning of mathematics.